DETERMINAN FRAUD DIAMOND DALAM MENDETEKSI FINANCIAL STATEMENT FRAUD DAN NILAI PERUSAHAAN - Satria Rukmana, Heru (Sekolah Tinggi Ilmu Ekonomi Dewantara, 2018)
The purpose of this research is to analyze the determinant of fraud diamond that is pressure, opportunity, rationality and capability to financial fraud statement and its impact to company value. The sample of research is 66 manufacturing industry companies indicated to perform financial fraud statement. Methods of data analysis using simultaneous regression with panel data. the result of the research shows: 1) gross profit margin has positive effect to financial statement fraud, 2) frequency of cash flow is not affect to fraud financial report, 3) Board of commissioner have positive and significant effect to fraudulent financial report. 4) Return on asset has positive and significant effect on fraud financial report 5) Receiveable has no effect and positive to fraudulent financial report 6) Independent board of commissioner has negative and significant effect on fraud financial report 7) Independent board of commissioner has positive effect on financial fraud statement, 8) total accruals have a positive and significant effect on financial statement fraud, 9) majority ownership positively and positively influences to financial statement fraud, 10) earnings management negatively affects company value.